An investigation into the development of a marine and coastal mining strategy framework for South Africa - LaBuschagne, Carel Johannes Frederick (My University, 2010)
The concept of marine and coastal mining is not well defined in South Africa; therefore this dissertation investigates the lack of rules in marine and coastal mining and the possible development of a marine and coastal mining strategy or policy. Subsequently, the research has resulted in five major actions and consequently a summary of the research process to identify and formulate a marine and coastal mining strategy framework. The first action was to evaluate relevant concepts in the marine and coastal environment. It also looked at the policy environment and environmental policy in mining and sustainable development. It was also imperative to evaluate strategy within the marine, coastal and mining environment on both international and national level. This resulted in the second action to analyse these evaluations. Five major gaps in the South African policy environment were identified with specific reference to marine and coastal mining. The next question was to identify possible solutions for South Africa for these gaps, therefore the third action was aimed at formulating three options to address the marine and coastal mining gap. The option preferred is a strategy framework to implement a meaningful marine mining and coastal mining strategy. The marine and coastal mining strategy framework includes: 1) Scope, objectives and principles; 2) Marine mining strategy; 3) Coastal mining strategy; and 4) Implementation strategy. The marine mining strategy and coastal mining strategy do not only identify actions but also identify the introduction of joint authority approach, further research, development of specific technical guidelines and dealing with conflicts. The investigation concludes by elaborating on the process followed and achieving the research goal of a strategy. The investigation is finally rounded off by formulating five recommendations which should be considered and executed by the Department of Minerals and Energy. It includes the development and implementation of the marine and coastal mining strategy framework, conduct research on marine mining and coastal mining matters, develop guidelines for both marine mining and coastal mining, initiate the development of future rules for marine and coastal mining, and also initiate the development of mine environmental policy and an exclusive economic zone strategy.